Wood-derived self-supporting composite electrode and preparation method and application thereof

Through the preparation method of wood-derived support composite electrodes, the problem of limitation of existing electrocatalyst substrates is solved, and efficient catalytic activity and selectivity in electrocatalytic fully decomposed water is achieved, with good commercial value and application prospects.

CN119506943AInactive Publication Date: 2025-02-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411756687.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The substrates of existing electrocatalysts are limited by metal foams, carbon cloths or semiconductors, which limit their catalytic activity and selectivity in electrocatalytic fully decomposed water.

Method used

The wood-derived supporting composite electrode is used to prepare a doped phosphorus matrix carbon loaded with transition metal phosphides through impregnation, carbonization and phosphating treatment of wood chips, transition metal salt solution and hydrochloric acid solution to form an electrode with a composite structure.

Benefits of technology

The electrode exhibits excellent catalytic activity and selectivity of target products (hydrogen and oxygen) in electrocatalytic total decomposition water, and the preparation process is simple and economical, and is easy to produce in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506943A_ABST
    Figure CN119506943A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to a wood-derived self-supporting composite electrode and a preparation method and application thereof.The preparation method comprises the steps that wood chips are mixed with a solution A and a solution B for dipping, the solution A is a transition metal salt solution, the solution B is a hydrochloric acid solution, and the wood chips loaded with transition metal salt are obtained; carbonizing the impregnated wood chips loaded with the transition metal salt to obtain matrix carbon loaded with the transition metal salt; carrying out phosphating treatment on the carbonized matrix carbon loaded with the transition metal salt by using sodium phosphite to obtain phosphorus-doped matrix carbon loaded with transition metal phosphide, namely the self-supporting composite electrode; and the catalyst has excellent catalytic activity and target product selectivity in the aspect of electro-catalytic full-decomposition of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and more specifically, to a wood-derived self-supporting composite electrode and a preparation method and application thereof. Background Art

[0002] As of 2024, fossil fuels still account for more than 80% of the global energy structure, and energy shortages and greenhouse effects are still increasing. Therefore, energy shortages and environmental pollution are still the two major problems facing human development. Making the most of renewable energy such as solar energy, wind energy, hydropower, geothermal energy, and tidal energy is the fundamental way to solve energy and environmental problems and achieve the goals of carbon peak and carbon neutrality. At present, although solar energy and other renewable energy power generation have made significant progress, transportation, metallurgy, cement, heating and other industries still have rigid CO2 emissions. Therefore, it is imperative to find renewable clean energy and develop green and efficient energy storage and conversion technologies. Hydrogen energy, as a renewable zero-carbon energy, has the characteristics of abundant resources, high calorific value, zero pollution, and storability. It is a bridge for transition and conversion between fossil energy and renewable energy, and is considered to be the energy with the most development potential in the future. Vigorously developing hydrogen energy can absorb renewable energy on a large scale and efficiently, improve the resilience of the energy system, replace fossil energy, reduce carbon emissions, and help achieve carbon peak and carbon neutrality. Among the many hydrogen production methods, water electrolysis is a green, efficient and highly selective hydrogen production method. In the face of the high energy consumption in the hydrogen production industry, the development of efficient, stable and inexpensive bifunctional hydrogen evolution (HER) and oxygen evolution (OER) electrocatalysts is the key to overcoming these practical problems. Although transition metal catalysts are highly active, their substrates are still limited to metal foams, carbon cloth or semiconductors. Summary of the invention

[0003] The present application is provided to solve the above-mentioned defects existing in the prior art. A wood-derived self-supporting composite electrode and its preparation method and application are needed, which can solve the problem that the substrate is limited to metal foam, carbon cloth or semiconductor, and has excellent catalytic activity and target product (hydrogen and oxygen) selectivity in electrocatalytic water splitting.

[0004] In a first aspect of the present application, a method for preparing a wood-derived self-supporting composite electrode is provided, the method comprising: impregnating wood chips with a mixture of a solution A and a solution B, wherein the solution A is a transition metal salt solution and the solution B is a hydrochloric acid solution, to obtain wood chips loaded with transition metal salts; carbonizing the impregnated wood chips loaded with transition metal salts to obtain matrix carbon loaded with transition metal salts; and phosphating the carbonized matrix carbon loaded with transition metal salts with sodium phosphite to obtain phosphorus-doped matrix carbon loaded with transition metal phosphides, i.e., the self-supporting composite electrode.

[0005] In a second aspect of the present application, a self-supporting composite electrode is provided which is prepared by the preparation method described in any embodiment of the present application.

[0006] The third aspect of the present application provides an application of the self-supporting composite electrode described in any embodiment of the present application in electrocatalytic water splitting.

[0007] The wood-derived self-supporting composite electrodes provided in the various embodiments of the present application, as well as their preparation methods and applications, comprise wood chips that are loaded with transition metal salts by impregnation and then carbonized and phosphated to obtain a carbon-doped matrix, and also obtain transition metal phosphides, to form a composite electrode with a composite structure; the obtained self-supporting composite electrode has excellent catalytic activity and selectivity for target products (hydrogen and oxygen) in electrocatalytic complete water decomposition; the preparation process is simple and economical, easy for industrial production, and shows good commercial value and broad application prospects; the obtained self-supporting composite electrode has excellent electrocatalytic complete water decomposition performance, which can help achieve the goals of carbon peak and carbon neutrality. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0009] Figure 1 Optical photographs showing natural poplar wood and self-supporting composite electrodes for electrocatalytic water splitting according to different embodiments of the present application: (a) NC; (b) CW; (c) PCW; (d) Ni2P-PCW; (e) FeP y -PCW; (f)Ni2P / FeP y -PCW; Figure 2 The linear voltammetric curves according to different embodiments of the present application are shown as follows: (a) standard curve of the test equipment; (b) working curve of the test equipment and electrode materials; Figure 3 The contact angles of the self-supporting composite electrodes for electrocatalytic water splitting according to different embodiments of the present application are shown: (a) CW; (b) PCW; (c) Ni2P-PCW; (d) FeP y -PCW; (e)Ni2P / FeP y -PCW; Figure 4The HER polarization curve of the self-supporting electrode according to the embodiment of the present application in 1.0 M KOH solution is shown: 0.5 mV / s; Figure 5 The OER polarization curve of the self-supporting electrode according to the embodiment of the present application in 1.0 M KOH solution is shown: 0.5 mV / s; Figure 6 The symmetrical Ni2P / FeP according to the embodiment of the present application is shown. y -Stability test curve of PCW self-supporting composite electrode in 1.0 M KOH solution: 1.45 V vs RHE; Figure 7 The Ni2P / FeP according to the embodiment of the present application is shown y -HER polarization curve of PCW self-supporting composite electrode before and after stability test in 1.0 M KOH solution: 0.5 mV / s; Figure 8 The Ni2P / FeP according to the embodiment of the present application is shown y -OER polarization curve of PCW self-supporting composite electrode before and after stability test in 1.0 M KOH solution: 0.5 mV / s; Fig. 9 The Ni2P / FeP according to the embodiment of the present application is shown y -OER polarization curve of PCW self-supporting composite electrode before and after stability test in 1.0 M KOH solution: 0.5 mV / s; Fig.10 The Ni2P / FeP according to the embodiment of the present application is shown y -XRD pattern of PCW free-standing composite electrode. DETAILED DESCRIPTION

[0010] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation methods. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but are not intended to limit the present application.

[0011] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0012] According to an embodiment of the present application, a method for preparing a wood-derived self-supporting composite electrode is provided, the preparation method comprising: impregnating wood chips with a mixture of a solution A and a solution B, wherein the solution A is a transition metal salt solution and the solution B is a hydrochloric acid solution, to obtain wood chips loaded with transition metal salts; carbonizing the impregnated wood chips loaded with transition metal salts to obtain matrix carbon loaded with transition metal salts; and phosphating the carbonized matrix carbon loaded with transition metal salts with sodium phosphite to obtain phosphorus-doped matrix carbon loaded with transition metal phosphides, i.e., the self-supporting composite electrode.

[0013] In some embodiments, wood chips are obtained by cutting natural wood in a direction perpendicular to the growth direction of the wood. The raw material is renewable natural wood, which is cheap and widely available, thus realizing high-value conversion of forest resources.

[0014] In some embodiments, the transition metal salt solution includes one or both of nickel salt and iron salt, such as one or more of nickel nitrate, iron nitrate, nickel chloride hexahydrate and iron chloride hexahydrate.

[0015] In some embodiments, the concentration of the transition metal salt solution is 0.05-0.5 mol / L; the concentration of the hydrochloric acid solution is 0.5-3.0 mol / L.

[0016] In some embodiments, the mass ratio of solution A to solution B is 8-10:1; solution A and solution B form a mixed solution, and the mass ratio of wood chips to the mixed solution is 3:200.

[0017] In some embodiments, the immersion temperature is 60-100° C., and the immersion time is 10-15 h.

[0018] In some embodiments, the temperature of the carbonization treatment is 700-1000° C., and the carbonization time is 1-6 h.

[0019] In some embodiments, the mass ratio of the matrix carbon loaded with transition metal salt to sodium phosphite after carbonization is 1:0.5 to 1:5.

[0020] In some embodiments, the phosphating temperature is 350-900° C., and the carbonization time is 2-6 h.

[0021] According to an embodiment of the present application, there is also provided a self-supporting composite electrode prepared by the preparation method described in any embodiment of the present application.

[0022] According to an embodiment of the present application, there is also provided an application of the self-supporting composite electrode described in any embodiment of the present application in electrocatalytic complete water decomposition.

[0023] Comparative Example 1 In this comparative example, natural poplar wood is used as raw material, and a self-supporting composite electrode of carbonized wood (CW) is prepared through a high-temperature carbonization process. The specific operation steps include: high-temperature carbonization: dry poplar wood is placed in a porcelain boat, and then the porcelain boat is placed in a tubular furnace with a flowing N2 atmosphere, and the temperature is increased to 260°C at a heating rate of 5°C / min and kept warm for 2 h, and then the temperature is increased to 800°C at the same heating rate and kept warm for 6 h. After the temperature of the tubular furnace drops to room temperature, the carbonized self-supporting composite electrode (CW) is taken out.

[0024] Comparative Example 2 In this comparative example, natural poplar wood is used as raw material, and a P-doped carbonized wood (PCW) self-supporting composite electrode is prepared through high-temperature carbonization and low-temperature phosphating processes. The specific operation steps are as follows: (1) High-temperature carbonization: Put the dried poplar wood into a porcelain boat, and then place the porcelain boat in a tubular furnace with flowing N2 atmosphere. Heat the temperature to 260 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h. Then heat the temperature to 800 °C at the same heating rate and keep it at that temperature for 6 h. After the temperature of the tubular furnace drops to room temperature, take out the carbonized self-supporting composite electrode (CW). (2) Low-temperature phosphating: Take the CW composite electrode and sodium hypophosphite in step (1) and place them on both ends of a porcelain boat (the mass ratio of the CW composite electrode to sodium hypophosphite is 1:10). Then place the porcelain boat in a tubular furnace with a flowing N2 atmosphere (the CW composite electrode is close to the gas outlet). Then, heat the mixture to 350 °C at a heating rate of 5 °C / min and keep the temperature for 2 h. After the temperature of the tubular furnace drops to room temperature, take out the PCW self-supporting composite electrode.

[0025] Example 1 In this embodiment, natural poplar wood is used as raw material, and a self-supporting composite electrode of Ni2P nanoparticles loaded on P-doped carbonized wood (Ni2P-PCW) is prepared through hydrothermal impregnation, high-temperature carbonization and low-temperature phosphating processes. The specific operation steps are as follows: (1) Hydrothermal impregnation: Pour a mixed solution of solution A1 (0.2 M NiCl2·6H2O) and solution B (1.0 M HCl) into a stainless steel reactor (the mass ratio of solution A1 to solution B is 9:1), then put the dried poplar wood chips into the mixed solution (the mass ratio of poplar wood chips to the mixed solution is 3:200), and then keep it at 80 °C for 12 h to perform hydrothermal impregnation on the wood. After the reactor is cooled to room temperature, take out the poplar wood chips and dry them; (2) High-temperature carbonization: Place the poplar wood chips in step (1) into a porcelain boat, and then place the porcelain boat in a tubular furnace with a flowing N2 atmosphere. Heat the temperature to 260 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h. Then heat the temperature to 800 °C at the same heating rate and keep it at that temperature for 6 h. After the temperature of the tubular furnace drops to room temperature, take out the carbonized self-supporting composite electrode (Ni-CW). (3) Low-temperature phosphating: Take the Ni-CW composite electrode and sodium hypophosphite in step (2) and place them on both ends of a porcelain boat (the mass ratio of the Ni-CW composite electrode to sodium hypophosphite is 1:10). Then place the porcelain boat in a tubular furnace with a flowing N2 atmosphere (the Ni-CW composite electrode is close to the gas outlet). Then, heat the mixture to 350°C at a heating rate of 5°C / min and keep the temperature for 2 h. After the temperature of the tubular furnace drops to room temperature, take out the Ni2P-PCW self-supporting composite electrode.

[0026] Example 2 In this embodiment, natural poplar wood is used as raw material, and FeP is prepared through hydrothermal impregnation, high temperature carbonization and low temperature phosphating process. y Nanoparticles loaded on P-doped carbonized wood (FeP y -PCW) self-supporting composite electrode, the specific operation steps are as follows: (1) Hydrothermal impregnation: Pour a mixed solution of A2 solution (0.2 M FeCl3·6H2O) and B solution (1.0 M HCl) into a stainless steel reactor (the mass ratio of A2 solution to B solution is 9:1), then put the dried poplar wood chips into the mixed solution (the mass ratio of poplar wood chips to the mixed solution is 3:200), and then keep it at 80 °C for 12 h to perform hydrothermal impregnation on the wood. After the reactor is cooled to room temperature, take out the poplar wood chips and dry them; (2) High-temperature carbonization: Place the poplar wood chips in step (1) into a porcelain boat, and then place the porcelain boat in a tubular furnace with a flowing N2 atmosphere. Heat the temperature to 260 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h. Then heat the temperature to 800 °C at the same heating rate and keep it at that temperature for 6 h. After the temperature of the tubular furnace drops to room temperature, take out the carbonized self-supporting composite electrode (Fe-CW). (3) Low-temperature phosphating: Take the Fe-CW composite electrode and sodium hypophosphite in step (2) and place them at both ends of the porcelain boat (the mass ratio of the Fe-CW composite electrode to the sodium hypophosphite is 1:10), then place the porcelain boat in a tubular furnace with flowing N2 atmosphere (the side of the Fe-CW composite electrode close to the gas outlet), then heat it to 350 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h. After the temperature of the tubular furnace drops to room temperature, take out the FeP y -PCW self-supporting composite electrode.

[0027] Example 3 In this embodiment, natural poplar wood is used as raw material, and Ni2P and FeP are prepared through hydrothermal impregnation, high temperature carbonization and low temperature phosphating process. y Nanoparticles loaded on P-doped carbonized wood (Ni2P / FeP y -PCW) self-supporting composite electrode, the specific operation steps are as follows: (1) Hydrothermal impregnation: Pour a mixed solution of A3 solution (0.1 M NiCl2·6H2O + 0.1 M FeCl3·6H2O) and B solution (1.0 M HCl) into a stainless steel reactor (the mass ratio of A3 solution to B solution is 9:1), then put the dried poplar wood chips into the mixed solution (the mass ratio of poplar wood chips to the mixed solution is 3:200), and then keep it at 80 °C for 12 h to perform hydrothermal impregnation on the wood. After the reactor is cooled to room temperature, take out the poplar wood chips and dry them; (2) High-temperature carbonization: Place the poplar wood chips in step (1) into a porcelain boat, and then place the porcelain boat in a tubular furnace with a flowing N2 atmosphere, heat the temperature to 260 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h, then heat the temperature to 800 °C at the same heating rate and keep it at that temperature for 6 h. After the temperature of the tubular furnace drops to room temperature, take out the carbonized self-supporting composite electrode (Ni / Fe-CW); (3) Low-temperature phosphating: Take the Ni / Fe-CW composite electrode and sodium hypophosphite in step (2) and place them at both ends of the porcelain boat (the mass ratio of Ni / Fe-CW composite electrode to sodium hypophosphite is 1:10), then place the porcelain boat in a tubular furnace with flowing N2 atmosphere (the side of the Ni / Fe-CW composite electrode close to the gas outlet), then heat it to 350 °C at a heating rate of 5 °C / min and keep it at that temperature for 2 h. After the temperature of the tubular furnace drops to room temperature, take out the Ni2P / FeP y -PCW self-supporting composite electrode.

[0028] The appearance of the self-supporting composite electrode prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3 is as follows: Figure 1 As shown, through Figure 1 It can be obtained that the self-supporting composite electrode was successfully prepared.

[0029] The self-supporting composite electrodes prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3 are shown in Table 1. The conductivity of the self-supporting composite electrodes prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3 is shown in Table 1. Figure 2 The contact angles of the self-supporting composite electrodes prepared in Comparative Example 1, Comparative Example 2, and Examples 1 to 3 are shown in FIG. Figure 3 As shown in Table 1 and Figure 2 , 3 It can be seen that the prepared free-standing electrode has high conductivity and low contact angle.

[0030] Table 1 Physical properties of self-supporting electrodes of different embodiments Figure 4 and Figure 5The HER and OER performances of the self-supporting electrodes of different embodiments are shown. The analysis results of HER and OER are summarized in Table 2. It can be found that the Ni2P / FePy-PCW electrode has the highest electrocatalytic activity.

[0031] Table 2 Electrochemical performance of self-supporting electrodes for overall water splitting Figure 6 , Figure 7 , Figure 8 The symmetric Ni2P / FeP prepared in Example 3 is shown y -Long-term stability testing of PCW self-supporting composite electrodes, which exhibit high Faradaic efficiency and electrocatalytic selectivity.

[0032] Depend on Fig. 9 It can be seen that the Ni2P / FePy-PCW self-supporting composite electrode prepared in Example 3 has an increased charge transfer resistance and a decreased electrocatalytic activity after the stability test. Fig.10 It can be obtained that the Ni2P / FePy-PCW self-supporting composite electrode prepared in Example 3 is composed of carbon, Ni2P, FeP4 and FeP phases, indicating that the matrix carbon of the self-supporting composite electrode of the present application is doped with phosphorus, and FePy includes FeP4 and FeP.

[0033] In addition, this application studies in detail the effects of solution A, solution B, immersion temperature (60-120°C), carbonization temperature (700-1000°C), carbonization time (1-6h), phosphating temperature (350-900°C) and phosphating time (2-6h) on the catalytic performance of electrode materials. The results show that the prepared self-supporting composite electrodes exhibit high electrocatalytic activity and selectivity.

[0034] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0035] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0036] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A method for preparing a wood-derived self-supporting composite electrode, characterized in that: The preparation method comprises: mixing wood chips with solution A and solution B for impregnation, wherein solution A is a transition metal salt solution and solution B is a hydrochloric acid solution, so as to obtain wood chips loaded with transition metal salts; carbonizing the impregnated wood chips loaded with transition metal salts to obtain matrix carbon loaded with transition metal salts; and phosphating the carbonized matrix carbon loaded with transition metal salts with sodium phosphite to obtain phosphorus-doped matrix carbon loaded with transition metal phosphides, i.e., a self-supporting composite electrode.

2. The preparation method according to claim 1, characterized in that: The transition metal salt solution includes one or both of nickel salt and iron salt.

3. The preparation method according to claim 1, characterized in that: The concentration of the transition metal salt solution is 0.05-0.5 mol / L; the concentration of the hydrochloric acid solution is 0.5-3.0 mol / L.

4. The preparation method according to claim 1, characterized in that: The mass ratio of solution A to solution B is 8-10:1; solution A and solution B form a mixed solution, and the mass ratio of wood chips to the mixed solution is 3:

200.

5. The preparation method according to claim 1, characterized in that: The immersion temperature is 60~100℃ and the immersion time is 10-15h.

6. The preparation method according to claim 1, characterized in that The temperature of carbonization treatment is 700-1000℃, and the carbonization time is 1-6 h.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the matrix carbon loaded with transition metal salt to sodium phosphite after carbonization is 1:0.5~1:

5.

8. The preparation method according to claim 1, characterized in that The phosphating temperature is 350-900°C, and the carbonization time is 2-6 h.

9. A self-supporting composite electrode prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the self-supporting composite electrode according to claim 9 in electrocatalytic overall water decomposition.